Multicenter prospective randomized controlled clinical trial comparing the pocket-creation method with and without single-clip traction of colonic endoscopic submucosal dissection - Morikawa, Takaaki; Nemoto, Daiki; Kurokawa, Tomohiro; Yamashina, Takeshi; Hayashi, Yoshikazu; Kitamura, Masafumi; Okada, Masahiro; Takezawa, Takahito; Nakajima, Yuki; Kowazaki, Yuka; Fukuda, Hisashi; Nomura, Tatsuma; Lazaridis, Nikolaos; Fukushima, Noriyoshi; Sunada, Keijiro; Yamamoto, Hironori (Endoscopy, 2024)
Background The pocket-creation method (PCM) was developed to overcome the technical difficulties of endoscopic submucosal dissection (ESD), although opening the pocket remains challenging. We developed a novel technique of PCM with single-clip traction (PCM-CT), which uses a reopenable clip as a traction device to maintain stability during the procedure. No prospective study has compared the efficacy of PCM-CT and PCM. This study aimed to investigate the effectiveness of PCM-CT vs. PCM in a randomized controlled trial.Methods This randomized controlled clinical trial was conducted at four Japanese institutions. Patients with superficial colorectal neoplastic lesions were included following Japanese guidelines for colorectal cancer. Seven moderately experienced endoscopists performed the ESD procedures using either PCM-CT or PCM.Results 100 patients were enrolled in the study. Compared with PCM, PCM-CT achieved significantly faster mean (SD) dissection speed (21.4 [10.8] vs. 27.0 [14.5] mm2/min [95%CI 0.5 to 10.7], P = 0.03), and reduced the mean procedure time (81.8 [57.9] vs. 64.8 [47.6] minutes [95%CI –38.2 to 4.3], P = 0.12) and pocket-opening time (37.8 [33.0] vs. 30.0 [28.9] minutes [95%CI –20.2 to 4.6], P = 0.22). En bloc and R0 resection rates were not significantly different between the two groups (100% vs. 100%, P >0.99; 100% vs. 96%, P = 0.50, respectively). No significant differences were observed in adverse events between the two groups.Conclusion ESD facilitated by the novel PCM-CT method appeared to be significantly faster than PCM. Both methods achieved high R0 resection rates.